Rapid antigenic tests to detect asymptomatic covid-19 infections - Jose Luis Turabian (Archives of Community Medicine and Public Health - Peertechz Publications, 2021)
Coronavirus disease 2019 (COVID-19) is a new disease, and obviously many things about it are not yet known for sure. But, the evolution of knowledge about it is being very fast. From not knowing anything about the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in early 2020, the scientific community has already managed to isolate it, sequence it, identify it, develop diagnostic tests and vaccines. However, as with any new epidemic, there are still many unknowns that will be resolved as it evolves and as scientists understand more about the behavior of the virus.